جهود المفسرين المغاربة في العناية بأصول التفسير: دراسة تأصيلية تطبيقية - شوية خيرة (University of Eloued, 2025)
الملخص: لقد كان اهتمام علماء المغرب العربي بعلم التفسير بالغاء حيث كثرت المؤلفات فيه منذ القرون الأولى، والتي لها وزنها وقيمتها في الساحة العلمية، بينما تأخر ظهور أصول التفسير عن التفسير بعدة قرون، الأمر الذي يدعو إلى تقصي مدى حضور أصول التفسير في التفاسير المغاربية، وكذا مدى اهتمامهم بها، وذلك من خلال محاولة الإجابة عن جملة من التساؤلات، وأبروها ما هي أهم المرتكزات التي انبنت عليها أصول التفسير عند المفسرين المغاربة؟ وعليه جاءت الأطروحة بعنوان: جهود المفسرين المغاربة في العناية بأصول التفسير دراسة تأصيلية تطبيقية، وهذا بهدف المساهمة في وضع أطر أساسية لأصول التفسير من خلال تتبع تطبيقات المفسرين المغاربة لها في تفاسيرهم، مع محاولة الاستخلاص والتحليل لمختلف مباحث علوم التفسير وأصوله التي برز فيها المفسرون المغاربة، وكان لهم الدور الكبير في ظهورها، وهذا من خلال رسم مخطط الدراسة في: مقدمة، ومبحث تمهيدي لنشأة وتطور التفسير المغاربي واتجاهاته والفصل الأول للتعريف بأصول التفسير، والفصل الثاني لاستمداد التفسير وأنواعه عند المفسرين المغاربة، والفصل الثالث الطرق التفسير وقواعده عند المفسرين المغاربة والخاتمة، والفهارس، ومن أهم النتائج التي توصلت إليها: أن التفسير في المغرب العربي تميز بتعدد اتجاهاته وتنوعها، كما أن للمفسرين المغاربة الفضل في إرساء المنهج الجامع أو الاتجاه الأثري النظري، وأن المكانة التي حظيت بها التفاسير المغاربية ليست من ضرب الصدف، بل لاعتمادهم على أصول متينة ورصينة في التفسير، جنبتهم الوقوع في الزلل، والتي من بينها اتباعهم لأحسن طرق التفسير، كما اعتمدوا على قواعد التفسير، سواء القواعد العامة، أو القواعد الترجيحية، مما أضفى على تفاسيرهم صبغة خاصة بهم، وتميزا، فكانت تفاسيرهم عظيمة جليلة، أشاد بها الكثير من العلماء. Résumé : فرنسية أو انجلزية The interest of the scholars of the Arab Maghreb by the science of interpretation was immense, as there are many books on it since the first centuries, which have their weight and value in the scientific arena, However, the emergence of the principles of interpretation was delayed by severaly centuries after the interpretation, which leads to check the attendance of the principle interpretation in the Maghrebis interpretation, and how it was their interest by it through the attempt of answering series of questions, the main one is: What are the anchors that were constructed on the principle interpretation by the Maghrebis interpreters? Thus, the thesis is entitled: The efforts of Maghrebis interpreters in paying attention to the principles of interpretation an applied original study. It came with the aim of contributing to the establishment of basic frameworks for the principles of interpretation by tracing Maghrebis interpreters applications of them in their interpretations, while attempting to extract and analyze the various topics of the sciences of interpretation and its origins. In which the Maghrebis interpreters became prominent, and they played a major role in its emergence, and accordingly the plan of the study was drawn up in: an introduction, an introductory research for the emergence and development of Maghrebis interpretation and its trends, the first chapter for introducing the principles of interpretation, the second chapter for deriving interpretation and its types according to Maghrebis interpreters, and the third chapter for the methods and rules of interpretation forthe Maghrebis interpreters, the conclusion, and the indexes. Among the most important findings that I reached: that interpretation in the Arab Maghreb was distinguished by the multiplicity and diversity of its trends, and that the Maghrebis interpreters had the credit for establishing the comprehensive approach or the theoretical archaeological trend, and that the position that Maghrebis interpretations enjoyed was not a coincidence. Rather, they relied on solid and sober principles of interpretation, which kept them from falling into mistakes, which included their following the best methods of interpretation. They also relied on the rules of interpretation, whether general rules or preferential rules, which gave their interpretations a character of their own and distinction, so their interpretations were great and majestic, many scholars praised it.
Thesis
Keywords: التفسير; المفسرين; علوم القرآن; المغرب العربي